Product selectivity in plasmonic photocatalysis for carbon dioxide hydrogenation - Xiao Zhang (Nature Portfolio, 2017)
Atmospheric CO2 can be transformed into valuable hydrocarbons by reaction with H2, but CO is the favoured kinetic product. Here, Liu and co-workers show that plasmonic rhodium nanoparticles not only reduce the activation energy for CO2hydrogenation, but also photo-selectively produce methane.